2015
DOI: 10.5578/mb.10106
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Antibiotic Susceptibilities of Uropathogenic Escherichia coli Isolates in Transition from CLSI to EUCAST

Abstract: Determination of treatment protocols for infections according to antimicrobial susceptibility test (AST) results is are important for controlling the problem of antibiotic resistance. Two standards are widely used in the world. One of them is Clinical Laboratory Standards Institute (CLSI) standards used in Turkey for many years and the other is the European Committee on Antimicrobial Susceptibility Testing (EUCAST) standards which is used in European Union member countries and came into use in 2015 in Turkey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A study from Turkey based on Imipenem disc diffusion also showed similar results. [ 5 ] The IS category remained unchanged irrespective of the guideline used (97/501 = 19.36%). The number of absolute resistant strains estimated by CLSI exceeded those by EUCAST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Turkey based on Imipenem disc diffusion also showed similar results. [ 5 ] The IS category remained unchanged irrespective of the guideline used (97/501 = 19.36%). The number of absolute resistant strains estimated by CLSI exceeded those by EUCAST.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-stream urine specimens from suspected UTIs were cultured on HiCrome UTI Agar (HiMedia, Mumbai, India). E. coli strains with significant colony counts (>10[ 5 ] CFU/ml) were included in the study for AST. AST was carried out on Mueller-Hinton agar (Becton Dickinson, Maryland, USA) using a lawn of McFarland 0.5 in normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted in Ankara in 2015, Süzük et al [35] found the highest resistance, based on CLSI criteria, against cefuroxime axetil (79.8%), ampicillin (67.1%), and ampicillin sulbactam (34.3%) [35]. According to EUCAST criteria, the highest resistance was reported against ampicillin (63.8%), TMP-SMX (27.0%), and ampicillin sulbactam (30.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained separately by each method showed that amikacin and trimethoprim-sulfamethoxazole susceptibility rates were the same. However, the susceptibility rates were significantly different for gentamicin, cefuroxime axetil, and levofloxacin (19). Kassim et al reported that the AST patterns of E. coli obtained according to the EUCAST 2015 and CLSI 2015 guidelines were similar, excluding AMC, nitrofurantoin, and amikacin.…”
Section: Discussionmentioning
confidence: 99%